Wetting state and mechanical property alteration for the Fe3Si films using rapid thermal annealing under various temperatures - Nattakorn Borwornpornmetee; Thawichai Traiprom; Takafumi Kusaba; Phongsaphak Sittimart; Hiroshi Naragino; Boonchoat Paosawatyanyong; Tsuyoshi Yoshitake; Nathaporn Promros (My University, 2023)
The current research demonstrates the modification of the wetting behavior and mechanical features as well as structure and morphology of Fe3Si films created via facing target sputtering by the rapid thermal annealing (RTA) with the set RTA temperatures (TRTA) of 200, 400, 600, and 800 °C. Following the RTA process, the crystallinity of Fe3Si developed under 400 °C or below. At the 600 °C and 800 °C TRTA, new crystal orientations emerged for FeSi and then β-FeSi2, respectively. Together with composition results, the Fe3Si films were proven to change into FeSi and then FeSi2 under a high TRTA regime. At temperatures of 600 °C and 800 °C, large crystallites, including the scraggly interface, were observed. The root-mean-square roughness roughened slightly according to the RTA process at TRTA of 600 °C or above. The hydrophobic properties of the Fe3Si film surfaces became hydrophilic after the RTA procedure at a TRTA value above 400 °C. The hardness value of the Fe3Si films evidently increased through RTA at 600 °C and 800 °C. Thus, above 400 °C, the RTA process significantly alters the physical features of as-created Fe3Si films.
Keywords: Root mean square; Wetting layer; Aluminum Alloys Composites Properties